Vitamin D deficiency is highly prevalent in COPD and correlates with variants in the vitamin D-binding gene. Issue 3 (8th December 2009) - Janssens, Wim; Bouillon, Roger; Claes, Bart; Carremans, Claudia; Lehouck, An; Buysschaert, Ian; Coolen, Johan; Mathieu, Chantal; Decramer, Marc; Lambrechts, Diether
Abstract : Introduction: Vitamin D deficiency has been associated with many chronic illnesses, but little is known about its relationship with chronic obstructive pulmonary disease (COPD). Objectives: Serum 25-hydroxyvitamin D (25-OHD) levels were measured in 414 (ex)-smokers older than 50 years and the link between vitamin D status and presence of COPD was assessed. The rs7041 and rs4588 variants in the vitamin D-binding gene ( GC ) were genotyped and their effects on 25-OHD levels were tested. Results: In patients with COPD, 25-OHD levels correlated significantly with forced expiratory volume in 1 s (FEV1 ) (r=0.28, p<0.0001). Compared with 31% of the smokers with normal lung function, as many as 60% and 77% of patients with GOLD (Global Initiative for Obstructive Lung Disease) stage 3 and 4 exhibited deficient 25-OHD levels <20 ng/ml (p<0.0001). Additionally, 25-OHD levels were reduced by 25% in homozygous carriers of the rs7041 at-risk T allele (p<0.0001). This correlation was found to be independent of COPD severity, smoking history, age, gender, body mass index, corticosteroid intake, seasonal variation and rs4588 (p<0.0001). Notably, 76% and 100% of patients with GOLD stage 3 and 4 homozygous for the rs7041 T allele exhibited 25-OHD levels <20 ng/ml. Logistic regression corrected for age, gender and smoking history further revealed that homozygous carriers of the rs7041 T allele exhibited an increased risk for COPD (OR 2.11; 95% CI 1.20 to 3.71; p=0.009). Conclusion: Vitamin D deficiency occurs frequently in COPD and correlates with severity of COPD. The data warrant vitamin D supplementation in patients with severe COPD, especially in those carrying at-risk rs7041 variants.